COORDINATION CHEMISTRY OF TITANIUM (IV) IN SILICATE GLASSES AND MELTS: IV. XANES STUDIES OF SYNTHETIC AND NATURAL VOLCANIC GLASSES AND TEKTITES AT AMBIENT TEMPERATURE AND PRESSURE - Farges F.; Brown G.E. (My University, 1997)
The coordination environment of Ti(IV) in seven natural and synthetic glasses of basaltic, trachytic, rhyolitic composition as well as four tektites has been studied using high-resolution Ti K-edge x-ray absorption near edge structure (XANES) spectroscopy at ambient temperature and pressure. Pre-edge features of Ti K-edge XANES spectra for these glasses suggest that Ti is the dominant Ti coordination in all volcanic glasses. However, in the less polymerized glasses studied (basaltic and trachytic), Ti is also important (30-50% of the total Ti) but Ti was not detected. In contrast, Ti is important in the most polymerized glasses (rhyolites and tektites) (from 30 to 60% of the total Ti depending on NBO/T) with Ti below the detection level (~10 at%).The local structure around Ti in the natural volcanic glasses is similar to that observed in compositionally similar synthetic silicate glasses and also in Ti-bearing silicate glass and melts with simpler composition. The presence of F, Cl, and H2O does not appear to affect the coordination of Ti, based on Ti K-edge XANES measurements of natural glasses bearing these volatile components. In contrast, the presence of nonbridging oxygens (produced by network modifiers) favors Ti in these glass/melts. In parallel, Ti is important when nonbridging oxygens are at small concentrations (NBO/T < 0.1). Ti is detected (i.e., when present < 10% of the total Ti) when alkaline-earths are dominant over alkalis, in agreement with bond-valence predictions for Ti-bearing silicate glass/melts below TiO2 saturation.The abundance of Ti in these silicate glasses (and presumably their melts) is in sharp contrast with the rarity of this Ti coordination state in common rock-forming minerals. Titanium cannot readily enter the structure of most rock-forming minerals, because it is present dominantly as titanyl-bearing (Ti#O) units in most natural magmas. In contrast, Ti and Ti (present, respectively, in basic and acidic magmas) are better able to enter inosilicates, but these coordination states represent only a fraction of the Ti in basalts, explaining the usually moderate level of incompatibility of Ti during magmatic differentiation. Finally, Ti transforms to Ti during crystallization of Ti-rich minerals (ilmenite, rutile, pyrochlore).